Effect of On-Time Delivery, Tracking, and Cargo Insurance on Customer Loyalty through Customer Satisfaction - Isti Fani; Edi Abdurachman; Juliater Simarmata; Nofrisel Nofrisel (Goodwood Publishing, 2026)
Purpose: This research investigates how on-time delivery, tracking systems, and cargo insurance influence customer loyalty via customer satisfaction among logistics service users in Jakarta, Indonesia. Methodology: This research utilized a quantitative, cross-sectional approach with purposive sampling of 318 logistics customers in Jakarta (62% business and 38% individual consumers). Five constructs were measured using validated seven-point Likert scales and analyzed via SEM-PLS using SmartPLS with 5,000 bootstrap resampling. Results: On-time delivery significantly affected customer satisfaction (β = 0.326, p < 0.001) and loyalty (β = 0.386, p < 0.001). Tracking systems and cargo insurance also significantly influenced satisfaction (β = 0.285 and 0.249, p < 0.001) and loyalty (β = 0.205, p = 0.002; and β = 0.138, p = 0.009). Customer satisfaction significantly predicted loyalty (β = 0.460, p < 0.001). All mediation paths showed partial mediation (VAF = 28.0%–45.5%). The model explained 79.0% of the satisfaction and 77.4% of the loyalty variance. Conclusions: Customer satisfaction partially mediates the effect of logistics service attributes on loyalty. Building on previous studies, this study categorizes on-time delivery, tracking systems, and cargo insurance into three separate trust dimensions operational, informational, and financial that influence satisfaction and loyalty. Limitations: This study was limited to logistics customers in Jakarta, employed a cross-sectional design, and examined only three service attributes, excluding other potential determinants of loyalty. Contributions: This study enhances the literature on logistics service quality by introducing a three-dimensional trust framework, offering practical insights for providers in Jakarta.